Melanoma-derived iPCCs show differential tumorigenicity and therapy response - Bernhardt, Mathias; Novak, Daniel; Orouji, Elias; Knappe, Nathalie; Weina, Kasia; Reith, Maike; Gebhardt, Christoffer; Umansky, Viktor; Utikal, Jochen (Stem cell reports, 2017)
Summary. A point mutation in the BRAF gene, leading to a constitutively active form of the protein, is present in 45%-60% of patients and acts as a key driver in melanoma. Shortly after therapy induction, resistance to MAPK pathway-specific inhibitors develops, indicating that pathway inhibition is circumvented by epigenetic mechanisms. Here, we mimicked epigenetic modifications in melanoma cells by reprogramming them into metastable induced pluripotent cancer cells (iPCCs) with the ability to terminally differentiate into non-tumorigenic lineages. iPCCs and their differentiated progeny were characterized by an increased resistance against targeted therapies, although the cells harbor the same oncogenic mutations and signaling activity as the parental melanoma cells. Furthermore, induction of a pluripotent state allowed the melanoma-derived cells to acquire a non-tumorigenic cell fate, further suggesting that tumorigenicity is influenced by the cell state.